2010
DOI: 10.2174/138161210790170148
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Vaccines: Emphasis on Pediatric Cancers

Abstract: The success that vaccines have had in the fight with infectious diseases has not been mirrored in their use in the fight against cancer. The major differences are that cancer vaccines have been tested in the therapeutic rather than the prophylactic setting, and in older adults rather than in the pediatric population. Cancers, as well as current standard treatments, are highly immunosuppressive, which further compromises the success of therapeutic vaccines. Cancer is considered to be primarily a disease of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 53 publications
(85 reference statements)
0
5
0
Order By: Relevance
“…Most gliomas can be categorized as either low-grade (LGGs) or high-grade gliomas (HGGs). The latter includes anaplastic astrocytoma (AA) and glioblastoma multiforme (GBM) [6,21,22].…”
Section: Therapeutic Vaccination For Pediatric Cancer: the Past Anmentioning
confidence: 99%
See 4 more Smart Citations
“…Most gliomas can be categorized as either low-grade (LGGs) or high-grade gliomas (HGGs). The latter includes anaplastic astrocytoma (AA) and glioblastoma multiforme (GBM) [6,21,22].…”
Section: Therapeutic Vaccination For Pediatric Cancer: the Past Anmentioning
confidence: 99%
“…Although it is challenging to assess survival benefit in single-arm studies, several of the clinical trials listed in Table 1 have reported unexpectedly long survival times. For example, De Vleeschouwer et al noted that DC vaccine-treated patients under the age of 35 had an overall survival (OS) of 15.3 months, which was an improvement compared to a Children’s Cancer Group trial which reported that all patients with recurrent malignant glioma died within 1 year [6,46]. In patients with Ewing’s sarcoma, the combination of tumor lysate/KLH-pulsed DC vaccinations with autologous lymphocytes and rhIL-7 administered following standard antineoplastic therapy resulted in higher survival rates and lower recurrence rates compared with patients receiving standard antineoplastic therapy alone [47].…”
Section: Therapeutic Vaccination For Pediatric Cancer: the Past Anmentioning
confidence: 99%
See 3 more Smart Citations